PENINGKATAN SIKAP BERSAHABAT/ KOMUNIKATIF DAN PRESTASI BELAJAR PADA TEMA 8 DAERAH TEMPAT TINGGALKU MENGGUNAKAN MODEL PROBLEM BASED LEARNING DENGAN BANTUAN MEDIA GAMBAR SERI - Permana, Bayu Adji; Pamujo, Pamujo; Badarudin, Badarudin (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2019)
Background of this research is the low communicative friendly attitude and learning achievement of students. This study aims to improve the friendliness / communicative attitude and learning achievement of students through the Problem Based Learning (PBL) model with the help of serial image media. This classroom action research is carried out in 2 (two) cycles, each cycle consisting of two meetings with each meeting one lesson plan. This research consists of stages of planning, action, observation, and reflection. The subjects of this study were forth grade students, consist of 13 male students and 18 female students. The data collection tool uses evaluation tests, teacher activity sheets, friendly/communicative attitude observation sheets of students as well as students’ friendly/communicative attitude scale sheets. The results of the improvements that occur can be seen in each cycle. The results of this study indicated that the use of the Problem Based Learning (PBL) model with the help of serial image media can improve friendliness / communicative attitudes and learning achievements of the theme students of the 8 areas where I live in the fourth grade students of SD Negeri 2 Sokaraja Tengah Sokaraja District, Banyumas.